HLA Genotyping using Next Generation Sequencing - Lucan C.; Pop Laura-Ancuta; Florian A.; Pileczki Valentina; Petrushev B.; Dima Delia; Frinc Ioana; Berindan-Neagoe Ioana; Irimie A.; Berce C.; Florian I.-S; Bojan Anca; et al. (Sciendo, 2016)
From an oncological perspective, the second most common malignancies in children are brain tumors. Despite the recent therapeutic breakthroughs in this field, concerning surgery, radiotherapy and chemotherapy alike, some cases still have poor outcomes in curability. This is especially the case in patients with high-risk histological types of tumors, and those suffering from residual, remitting and disseminated diseases. Due to the unique neuroanatomical emplacement of brain tumors and their aggressive infiltrative behavior, their total removal remains a demanding task. This can be perceived in the high rates of failure treatment and disease recurrence. Furthermore, the adjacent healthy brain tissue is inevitably damaged in the surgical process of effectively removing these tumors. Thus, stem cell transplantation may be a viable solution for the clinical management of these malignancies, as proven by various recent breakthroughs. In the current concise review, we present the role of next generation sequencing in HLA typing for stem cell transplantation in primary CNS pediatric malignancies.